Isolation and Characterization of Five Erwinia amylovora Bacteriophages and Assessment of Phage Resistance in Strains of Erwinia amylovora - Schnabel, Elise L. (American Society for Microbiology, 2001)
Phages able to infect the fire blight pathogen Erwinia amylovora were isolated from apple, pear, and raspberry tissues and from soil samples collected at sites displaying fire blight symptoms. Among a collection of 50 phage isolates, 5 distinct phages, including relatives of the previously described phages φEa1 and φEa7 and 3 novel phages named φEa100, φEa125, and φEa116C, were identified based on differences in genome size and restriction fragment pattern. φEa1, the phage distributed most widely, had an approximately 46-kb genome which exhibited some restriction site variability between isolates. Phages φEa100, φEa7, and φEa125 each had genomes of approximately 35 kb and could be distinguished by their EcoRI restriction fragment patterns. φEa116C contained an approximately 75-kb genome. φEa1, φEa7, φEa100, φEa125, and φEa116C were able to infect 39, 36, 16, 20, and 40, respectively, of 40 E. amylovora strains isolated from apple orchards in Michigan and 8, 12, 10, 10, and 12, respectively, of 12 E. amylovora strains isolated from raspberry fields (Rubus spp.) in Michigan. Only 22 of 52 strains were sensitive to all five phages, and 23 strains exhibited resistance to more than one phage. φEa116C was more effective than the other phages at lysing E. amylovora strain Ea110 in liquid culture, reducing the final titer of Ea110 by >95% when added at a ratio of 1 PFU per 10 CFU and by 58 to 90% at 1 PFU per 10(5) CFU.